2021
DOI: 10.3390/jcm11010159
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Calprotectin Is Increased in Stroke

Abstract: Background: While there have been major advances in unveiling the mechanisms comprising the ischemic cascade of CNS, stroke continues to be a significant burden. There is a need to extend the focus toward peripheral changes, and the brain–gut axis has recently gained much attention. Our study aimed to evaluate gut inflammation and its association with blood variables in stroke using fecal calprotectin (FC). Methods: Fecal samples were obtained from 27 stroke patients and 27 control subjects. FC was quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…We have reported increase in stroke patients of fecal calprotectin [33], which binds to and sequesters Zn, Mn, Ni, Cu, and Fe in the extracellular milieu through the action of metal-binding sites [56], and our present study showed that gut microbiome in stroke patients became enriched in the nickel transport system and the iron transport system.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…We have reported increase in stroke patients of fecal calprotectin [33], which binds to and sequesters Zn, Mn, Ni, Cu, and Fe in the extracellular milieu through the action of metal-binding sites [56], and our present study showed that gut microbiome in stroke patients became enriched in the nickel transport system and the iron transport system.…”
Section: Discussionsupporting
confidence: 65%
“…We have previously collected blood samples from stroke patients and analyzed various parameters; a notable finding is low levels of albumin and lymphocytes [ 33 ]. Albumin and lymphocytes serve as markers of prognostic nutritional index (PNI), and depletion of both markers is associated with poor functional outcome [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Korean study, 27 stroke patients had significantly higher levels of fecal calprotectin in their feces than in the controls. This finding raises the possibility that elevated fecal calprotectin is linked to consciousness and systemic response in stroke patients [36].…”
Section: Discussionmentioning
confidence: 96%
“…Stroke patients show increased levels of fecal calprotectin which positively correlates with high concentrations of serum inflammatory C-reactive protein. Moreover, fecal calprotectin amounts negatively correlate with serum albumin levels and the Glasgow Coma Scale which is suggested as an indicator of intestinal inflammation ( 43 ). Thus, activated neutrophils after stroke can increase intestinal inflammation and fecal calprotectin can be a promising biomarker for diagnosing intestinal inflammation.…”
Section: Stroke Changes Intestinal Microflora and Increases Inflammat...mentioning
confidence: 99%